Analysis of The Application of Risk Management in PT. Pertamina TBBM Tanjung Priok to Improve Non-Financial Firm (Case Study: Tank Construction X - Tanjung Priok) - Asa, M. Fanshurullah; Pakpahan, Yessy Rama Natalia; Sabila, Okfi Risa (Syntax Corporation, 2024)
PT Pertamina TBBM Tanjung Priok - Plumpang is one of the downstream oil facilities that plays an important role in the distribution and distribution of fuel for the community. Because, about 20% of the daily fuel needs in Indonesia are supplied from TBBM Tanjung Priok - Plumpang owned by PT Pertamina (Persero). In the course of time, many incidents (fire, etc.) within the scope of TBBM Plumpang. Therefore, this research aims to examine the application of Risk Management in the company PT Pertamina TBBM Tanjung Priok - Plumpang. This research uses a qualitative approach conducted through a process of interviews and direct observation. The purpose of applying Risk Management to this company is to identify what risks are involved in Risk Management within the scope of PT Pertamina TBBM Tanjung Priok-Plumpang by measuring the risk of probability and impact, and evaluating each existing risk, according to the case study of Tank X construction within the Tanjung Priok TBBM area. This research is expected to assist management in taking actions and responses to reduce the negative impacts of the possibilities that will occur in the future and provide an assessment of the various risks that exist. The results of this study will contain risk classes ranging from high risk, medium risk, and low risk.